Lomba Sepak Bola Antar Kampung sebagai Media Kebersamaan dan Nasionalisme Masyarakat di Momentum Hari Kemerdekaan 2025 - Varadifha, Aisyah Putri, Neng Cahya Yulianti; Della Meira; Alfian Eka Nursanto; Gunawan; Samsul Anam; Ilyasya Saputra (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to describe the implementation of an inter-village soccer competition in celebration of Indonesia's Independence Day on August 17, 2025, and to examine its impact on the community. The event, held in Margaluyu Village, involved participants of all ages and was lively, with a high level of community involvement. The method used was qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The data obtained was then analyzed descriptively to present the factual conditions on the ground, particularly regarding social interaction, sportsmanship, and the values of solidarity reflected in the activity. The study results indicate that the inter-village soccer tournament not only serves as entertainment and healthy competition but also strengthens social bonds, fosters a culture of mutual assistance, and instills values of sportsmanship, discipline, and cooperation. Thus, this activity can be considered a strategic medium for strengthening social cohesion among the community while nurturing a spirit of nationalism through the momentum of the independence celebration.